2021
DOI: 10.1155/2021/6620427
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Multiple Tuned Mass Dampers for Road Bridges Taking into Account Bridge‐Vehicle Interaction, Random Pavement Roughness, and Uncertainties

Abstract: Road bridge designs are based on technical standards, which, to date, consider dynamic loading as equivalent static loads. Additionally, the few engineers who perform a dynamic analysis typically do not consider the effects of bridge-vehicle interaction and also simplify the road’s irregularity profile. Moreover, often, even when a simplified dynamic analysis is carried out and shows that there will be a high dynamic amplification factor (DAF), designers prefer to solve this problem by adopting high safety fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, the authors of [52] conducted optimization of TMD parameters for a building under seismic loading. Additionally, the authors of [53] focused on optimizing the parameters of MTMDs to minimize the maximum vertical displacement of road bridges subjected to vehicle trafc.…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…Furthermore, the authors of [52] conducted optimization of TMD parameters for a building under seismic loading. Additionally, the authors of [53] focused on optimizing the parameters of MTMDs to minimize the maximum vertical displacement of road bridges subjected to vehicle trafc.…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…Researchers have employed various numerical models and analysis methods to address vehicle-bridge interaction. Tese studies contribute to structural dynamics and encompass theoretical, numerical simulation, and real-world experimental aspects [1][2][3][4][5]. Tese investigations often utilize diferent vehicle models, such as moving force models, moving mass models, quarter-vehicle models, and fullvehicle models [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that, by applying adequate properties and positioning the TMD above water, it is possible to reduce the effects caused by dynamic actions moderately, while improving the effectiveness of energy generation. Other examples of TMD optimization in different types of structures subjected to different types of dynamic excitation can be found in [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%